Towards a new model of grit within a cognitive-affective framework of self-regulation - Alacia Armstrong; Elma van der Lingen; Riaan Lourens; Jeff Y-J. Chen (South African Journal of Business Management, 2018)
Grit – passion and perseverance for long-term goals – has been empirically shown to be a positive predictor of success across multiple contexts. The current study developed a new framework of grit within a framework of self-regulatory behaviours. Here, a qualitative approach was assumed to obtain interview data from chief innovation officers and chief information officers within technologically intensive industries. Empirical evidence was used to inductively determine the underlying cognitive-affective processing that influences gritty behaviour. Overall, six strategies were identified: temporal perspective, perpetual evaluation, motivational orientation, strength and resource gathering, system thinking and framing. Organisations may utilise the grit model developed here to enhance the grittiness of their innovation leaders by building effective cognitive-affective strategies.
Keywords: 650